2005
DOI: 10.1097/00006231-200501000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Reference data for 51Cr-EDTA measurements of the glomerular filtration rate derived from live kidney donors

Abstract: A model for the decline of GFR with age was produced in which GFR remains constant at 103.4 ml x min(-1) x (1.73 m2)(-1) until the age of 40 years and then declines at a rate of 9.1 ml x min(-1) x (1.73 m2)(-1) per decade. The data can be used to report the results of adult 51Cr-EDTA GFR investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
54
9
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 10 publications
15
54
9
6
Order By: Relevance
“…An increased prevalence of renal dysfunction has also been found amongst female patients in other studies of CV risk [5-11, 13, 14], and has usually been related to the fact that women are older than men in patient populations with MI and acute coronary syndromes. There was, however, no age difference between men and women in the present study, and there is no gender-related difference in renal function amongst healthy individuals [21,22]. There is a correction for gender-related differences in the Cockcroft-Gault formula due to the lower muscle mass and creatinine production amongst women [18], but the equation may nonetheless be less precise amongst women.…”
Section: Discussioncontrasting
confidence: 56%
“…An increased prevalence of renal dysfunction has also been found amongst female patients in other studies of CV risk [5-11, 13, 14], and has usually been related to the fact that women are older than men in patient populations with MI and acute coronary syndromes. There was, however, no age difference between men and women in the present study, and there is no gender-related difference in renal function amongst healthy individuals [21,22]. There is a correction for gender-related differences in the Cockcroft-Gault formula due to the lower muscle mass and creatinine production amongst women [18], but the equation may nonetheless be less precise amongst women.…”
Section: Discussioncontrasting
confidence: 56%
“…Other authors described the same variation for 51 Cr-EDTA-Cl ranging from 3.9% to 11.6% [17,[52][53][54]. In summary, we showed that plasma 51 Cr-EDTA-Cl is a very precise method to measure GFR in renal transplanted recipients.…”
Section: Discussionsupporting
confidence: 80%
“…Although the effect size was modest, each 1 SD higher CFPWV was associated with lower GFR roughly equivalent to 2 years of aging. 22 The persistence of an association between GFR and CFPWV in the absence of comparable relations between GFR and MAP or CPP suggests that aortic stiffness (as assessed by CFPWV) may be an important therapeutic target for the maintenance of adequate kidney function even beyond the potential beneficial effects of BP control.…”
Section: Discussionmentioning
confidence: 99%